PENGARUH PERMAINAN MAKE A MATCH (MENCARI PASANGAN) TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN ANAK USIA 56 TAHUN DI TK IT INSAN UTAMA I PEKANBARU - Hasanah Melwa; Zulkifli '; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The investigation is based on the observation in the field of the ability to know the concept of the number of children aged 5-6 years are still low. So it is necessary to make a match game usability to improve the ability to know the concept of numbers. This study aims to determine the effect of the game make a match in the ability to know the concept of the number of children aged 5-6 years in IT Tadika INSAN MAIN 1 Pekanbaru. The sample used in this study is 17 people. The data collection techniques were used that observation. Data were analyzed using t-test exam using SPSS 16.0. Hypothesis of the study is that there is a very significant influence on the ability to know the concept of the number of children aged 5-6 years in kindergarten IT INSAN MAIN 1 PEKANBARU after executing the game make a match. It can be seen from the results of data analysis diperolehi t = 18.796 and p = 0.000. Because p <0.05 then it can be concluded that there are distinction ability to recognize the concept of number of children aged 5-6 years are very striking after using the game make a match in play activity. So, it means Ho is rejected and Ha accepted indicate a very striking distinction between before and after the experiment using a make-game match against the ability to know the concept of the number of children aged 5-6 years in Tadika INSAN MAIN 1 Pekanbaru.Keywords: Games Make A Match, Capabilities Concept Numbers